The Ramsey numbers R(Tn, W6) for small n - Chen, Yaojun; Zhang, Yunqing; Zhang, Kemin (Utilitas Mathematica, 2005)
Let Tn denote a tree of order n and Wm a wheel of order m + 1. Baskoro et al. conjectured in [2] that if Tn is not a star, then R(Tn, Wm) = 2n - 1 for m ≥ 6 even and n ≥ m -1. We disprove the Conjecture in [6]. In this paper, we determine R(T n,W6) for n ≤ 8 which is the first step for us to determine R(Tn, W6) for any tree Tn.